(untitled) (Jurnal Ekonomi Pembangunan Widya Mandira, 2025)
Gross Regional Domestic Product (GRDP) as a measuring tool in knowing economic growth in a region/area. To increase GRDP, there are several causal factors as a driving force in increasing economic growth. Research was conducted to determine how the Human Development Index (HDI) and unemployment affect GRDP in 34 provinces in Indonesia. The research data uses cross-section data with the research method used is Ordinary Least Square (OLS). The results of the analysis show that partially HDI significantly affects GRDP and the unemployment rate significantly affects GRDP. Simultaneously, it is known that HDI and unemployment affect GRDP.